Recent advances in the removal of persistent organic pollutants (POPs) using multifunctional materials:a review. (October 2020) - Sun, Bohua; Li, Qianqian; Zheng, Minghui; Su, Guijin; Lin, Shijing; Wu, Mingge; Li, Chuanqi; Wang, Qingliang; Tao, Yuming; Dai, Lingwen; Qin, Yi; Meng, Bowen
Abstract: Persistent organic pollutants (POPs) have gained heightened attentions in recent years owing to their persistent property and hazard influence on wild life and human beings. Removal of POPs using varieties of multifunctional materials have shown a promising prospect compared with conventional treatments. Herein, three main categories, including thermal degradation, electrochemical remediation, as well as photocatalytic degradation with the use of diverse catalytic materials, especially the recently developed prominent ones were comprehensively reviewed. Kinetic analysis and underlying mechanism for various POPs degradation processes were addressed in detail. The review also systematically documented how catalytic performance was dramatically affected by the nature of the material itself, the structure of target pollutants, reaction conditions and treatment techniques. Moreover, the future challenges and prospects of POPs degradation by means of multiple multifunctional materials were outlined accordingly. Knowing this is of immense significance to enhance our understanding of POPs remediation procedures and promote the development of novel multifunctional materials. Graphical abstract: Image 1 Highlights: Removal of POPs using various multifunctional materials was reviewed. Thermal, electrochemical, photocatalytic remediation processes were summarized. Discussion of numerous underlying degradation mechanisms. Multiple impact factors of POPs degradation were analyzed. Future challenges and prospects for POPs remediation. Abstract : The removal of POPs using multifunctional materials was reviewed, with further discussion of the underlying mechanism, reaction kinetics, and future challenges.